Caregiving for Uganda's elders with disability: Using cross-sectional surveillance data to identify healthcare service gaps in low- and middle-income settings. Issue 3 (July 2018) - Bachani, Abdulgafoor M.; Bentley, Jacob A.; Zia, Nukhba; Galiwango, Edward; Lum, Jeremiah; Tuli, Gulnar; Ho, Shuen-En
Abstract: Background: Disability is highly prevalent in low-and-middle-income countries (LMICs), but there is a relative dearth of disability and caregiving research from LMICs. Objective: To examine type and severity of disability experienced by individuals 60 years and older, caregivers and type of caregiving assistance, and the interrelationships between sociodemographic factors involved in Uganda. Methods: Data was collected from two Eastern Ugandan districts using the WHO Disability Assessment Schedule 2.0. Data on availability of caregiver was analyzed for 816 participants with disability. Group comparisons and regression analyses examined differences based on caregiver availability. Results: Approximately 66% of individuals with disability had a caregiver. The mean age of those with a caregiver (74.7 ± 8.9 years) was statistically significantly ( p  = .0004) higher than that of individuals without caregiver (72.4 ± 8.2 years). Significant differences based on caregiver availability were found relative to sex ( p  = .009), age ( p ≤.001), education level ( p ≤.001), occupation ( p ≤.001) and head of household status ( p ≤.001). The most frequent types of disability were related to vision (78.4%) and ambulation (71.7%). Caregiving most often fell to family members. Logistic regression results showed that individuals over the age of 80 years were 2.51 times more likely to have a caregiver compared to those 60–69 years ( p ≤.001). Those in the highest wealth quintile were 1.77 times more likely to have a caregiver. Conclusions: Findings demonstrate gaps in caring for aging individuals with disabilities in LMICs and highlight the importance of understanding caregiver access in generating effective healthy aging initiatives and long-term care systems.